The effects of xylanase and arabinoxylan-oligosaccharides on the growth performance, non-specific immunity, hindgut microbial diversity and hindgut short-chain fatty acid production of African catfish, Clarias gariepinus - Gericke, Stephan Johann (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.